GOLD AND OIL PRICES VERSUS STOCK EXCHANGE: ACASE STUDY OF PAKISTAN - Najaf, Rabia; Najaf, Khakan; Yousaf, Salman (International Journal of Research -GRANTHAALAYAH, 2016)
Due to global financial crisis, around the all over the world all developing and under developing countries are facing the low trading profit. In most of the developing country like Pakistan, there is low investment level due to political instability. Due to this condition Karachi stock exchange has the worst sell .Karachi stock exchange is known as the oldest and more profitable stock exchange of Pakistan oil and gold prices are attracting investors towards there not in the stock exchange. This thing is the barrier for the progress of the development of the country. This paper is trying to expose that stock market is going to down due to these variables. For checking the impact of oil and gold prices on the Karachi stock exchange. We have used that secondary data for this study. For this purpose we have taken data from Karachi stock exchanges from the period of 1996 to 2013.We have applies correlation matrix for this purpose. the result has shown that KSE 100 has return is 0.014503 and GDP 0.058793 ,gold 0.012026 and oil 0.00919.karachi stock exchange return has standard value is 0.089982,while gold standard deviation 0.038716 and oil standard deviation value is 0.103375. The correlations have shown that in these markets there is not positive relationship.karachi stock exchange and GDP have inverse relationship with gold market. These results have also shown that oil growth has a significant relationship with KSE100 and GDP.For the predication correlation is not considering an authentic measure.